Dampak Corona Virus Disease 19 dan Obligasi Terhadap Nilai Tukar dan Sukuk di Indonesia - Mohammad Rofiuddin (Jurnal Ilmiah Ekonomi Islam, 2022)
The coronavirus-19 pandemic has become a threat to health and economic conditions, including a threat to transactions in the money market and the model market. The purpose of this study was to determine the magnitude of the effect of Covid-19 cases on Sukuk and the exchange rate; know the magnitude of the effect of exchange rates and bonds on Sukuk, and know the indirect relationship between Covid-19 and Sukuk. The data analysis method in this study uses a two-stage least square model approach, with a sample range from March 2020-November 2021. The results of the analysis conclude that the Covid-19 case influences the decline in the exchange rate, while the Covid-19 case has no effect on Sukuk. Other factors that affect Sukuk are the exchange rate and bonds. The results of the study also concluded that the Covid-19 case indirectly affected Sukuk through the exchange rate. This study contributes to the understanding of Sukuk, which can be influenced by many conditions, both coming from within the capital market itself and from external factors.